Relationship between Customer Experience and Digital Islamic-Only Banks: A Serial Mediation of Brand Trust and Brand Equity - Febriyanto, Ahmad; Taqiyyudin, Moh Shadam; Khoirunnisa, Annes Nisrina (El-Barka Journal of Islamic Economics and Business, 2023)
The main objective of this study is to investigate the construction of customer experience, trust, and brand equity in the relationships between Islamic Digital-Only Banks. This model aims to provide a solution to the problems faced by Islamic banking. The study utilized a sample of 262 respondents, who were given an online questionnaire for data collection. The research sample was selected using a convenience sampling approach and specifically focused on consumers of Islamic Digital-Only Banks in Central Java and the Special Region of Yogyakarta. The collected data were analyzed using the partial least squares structural equation modelling (SEM-PLS) method. The findings indicate that the process of creating trust in Islamic Digital-Only Banks brands through the provided customer experience acts as a precursor to enhancing brand equity. Consequently, this can contribute to fostering customer loyalty. Therefore, it is of utmost importance for Islamic Digital-Only Banks in Indonesia to prioritize delivering exceptional customer experiences. Key features such as simplicity in various processes and the company's promptness in resolving customer issues can serve as critical factors in building customer loyalty.